2012
DOI: 10.1242/jeb.061481
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of salinity and elevated CO2 levels on juvenile eastern oysters,Crassostrea virginica

Abstract: SUMMARYRising levels of atmospheric CO 2 lead to acidification of the ocean and alter seawater carbonate chemistry, which can negatively impact calcifying organisms, including mollusks. In estuaries, exposure to elevated CO 2 levels often co-occurs with other stressors, such as reduced salinity, which enhances the acidification trend, affects ion and acid-base regulation of estuarine calcifiers and modifies their response to ocean acidification. We studied the interactive effects of salinity and partial pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
149
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(169 citation statements)
references
References 94 publications
(131 reference statements)
15
149
4
1
Order By: Relevance
“…This suggests that well-fed healthy animals might display a higher capacity to compensate than starving individuals and that the physiological conditions of the specimens are essential (see section ''Synergistic impacts''). In contrast to Ries et al (2009) for the Eastern oyster C. virginica, Dickinson et al (2012) showed that shell growth of juvenile oysters were not affected by a pH decrease of up to -0.3 pH unit. However, the mechanical properties of the shells of the juveniles were altered under hypercapnic conditions, resulting in a reduced hardness and fracture resistance.…”
Section: Calcification and Shell Growthcontrasting
confidence: 64%
See 1 more Smart Citation
“…This suggests that well-fed healthy animals might display a higher capacity to compensate than starving individuals and that the physiological conditions of the specimens are essential (see section ''Synergistic impacts''). In contrast to Ries et al (2009) for the Eastern oyster C. virginica, Dickinson et al (2012) showed that shell growth of juvenile oysters were not affected by a pH decrease of up to -0.3 pH unit. However, the mechanical properties of the shells of the juveniles were altered under hypercapnic conditions, resulting in a reduced hardness and fracture resistance.…”
Section: Calcification and Shell Growthcontrasting
confidence: 64%
“…Oysters, the other economically very important group of species, appear less resistant than mussels to low pH conditions (three experiments showing negative impacts out of five), despite producing less soluble low-magnesium calcite shells. Moreover, the study showing no effect on oyster shell growth (Dickinson et al 2012) demonstrated that a pH decrease of less than -0.4 pH unit had significant effects on the shell hardness and fracture resistance. This could have importance consequences for this species in the field with a reduced capacity to resist to, for instance, strong currents and predators.…”
Section: Calcification and Shell Growthmentioning
confidence: 98%
“…It has been reported that ocean acidification will impact not only growth but also the ultrastructure of mollusk shells (Dickinson et al. 2012; Ivanina et al. 2013; Coleman et al.…”
Section: Introductionmentioning
confidence: 99%
“…2013) and fracture resistance after 11 weeks (Dickinson et al. 2012) in the juvenile oyster Crassostrea virginica (Dickinson et al. 2012; Ivanina et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation